Iron-catalyzed decarboxylative alkenylation of cycloalkanes with arylvinyl carboxylic acids via a radical process - Zhao, Jincan; Fang, Hong; Han, Jianlin; Pan, Yi (Beilstein Journal of Organic Chemistry, 2013)
A Fe(acac)3-catalyzed decarboxylative coupling of 2-(aryl)vinyl carboxylic acids with cycloalkanes was developed by using DTBP as an oxidant through a radical process. This reaction tolerates a wide range of substrates, and products are obtained in good to excellent yields (71–95%). The reaction also shows excellent stereoselectivity, and only trans-isomers are obtained.
Keywords: alkenylation; cycloalkanes; decarboxylative; Fe(acac)3; free radical; sp3 C–H bonds